Hubungan antara Politik dan Kebebasan menurut Hannah Arendt: The Relationship Between Politics and Freedom According to Hannah Arendt - Dose, Fransiskus; Waton, Fidelis Regi (STF Driyarkara - Diskursus, 2025)
Abstract Employing the qualitative method of literature review of primary and secondary sources, this paper sets out to reconstruct Hannah Arendt’s thought on the relation between politics and freedom. Freedom, in Arendt’s view, is not an objective nor result of politics, but rather something inherent in it. Action, speaking, and the public sphere are the three aspects and prerequisites for politics to be regarded as harboring freedom. Action and speaking presuppose plurality. Both involve not only one person, but the multitude, that inhabit the world. When many people act and speak, they are always free and inhabit the realm of politics. The public sphere makes it possible for the people to act, speak, and interact in freedom, and thus also to do politics. Arendt endorses the interactions in the Ancient Greek Agora as a model of the public sphere. Research on Arendt’s thought can significantly contribute to understanding politics. Politics is a never-ending action and speaking; it is a process. It never has an ending as through action, communication, and interaction, people can produce something new. For action, speaking, and interaction to be possible, the public sphere is a necessary condition. Keywords: Arendt, politics, freedom, plurality, action, speaking, public sphere. Abstrak Melalui pendekatan kualitatif, yakni telaah literatur baik primer maupun sekunder, tulisan ini hendak merekonstruksi pemikiran Hannah Arendt tentang hubungan antara politik dan kebebasan. Kebebasan, menurut Hannah Arendt, bukanlah tujuan dan hasil dari politik, melainkan sesuatu yang inheren dalam politik. Tiga aspek sekaligus kondisi agar politik dapat disebut mengandung kebebasan adalah tindakan, berbicara, dan ruang publik. Tindakan dan berbicara mengandaikan adanya pluralitas. Keduanya melibatkan bukan hanya satu orang, melainkan banyak orang, yang menempati dunia. Ketika banyak orang bertindak dan berbicara, mereka selalu bebas dan berada dalam konteks politik. Ruang publik memungkinkan manusia untuk bertindak, berbicara, dan berinteraksi dalam kebebasan, dan dengan demikian juga berpolitik. Arendt menjadikan interaksi di Agora pada zaman Yunani kuno sebagai model dari ruang publik. Penelitian tentang gagasan Arendt memberikan kontribusi signifikan untuk memahami politik. Politik adalah tindakan dan pembicaraan yang kontinu; ia adalah sebuah proses. Ia tidak pernah mencapai hasil akhir karena melalui tindakan, komunikasi, dan interaksi, manusia memiliki kemampuan untuk menghasilkan sesuatu yang baru. Untuk bisa bertindak, berbicara, dan berinteraksi, ruang publik adalah sebuah keharusan. Kata-kata Kunci: Arendt, politik, kebebasan, pluralitas, tindakan, berbicara, ruang publik.